Critical Digital Literacy: Technology in Education Beyond Issues of User Competence and Labour-Market Qualifications - Holger Pötzsch (tripleC: Communication, Capitalism & Critique)
The present contribution conducts an intervention in the study and practice of digital and media literacy. After reviewing key tenets of recent debates, I advance a specific understanding of the concept – critical digital literacy – that, as I argue, comprehensively addresses issues of knowledge, competencies, and skills in relation to digital technologies. In particular, I posit that critical thinking about educational and other values of ‘the digital’ needs to take structural aspects of the technology into account that are often eschewed in instrumental or commercially-driven approaches. To prepare pupils for their future lives requires a widest possible contextualisation of technology, including issues of exploitation, commodification, and degradation in digital capitalism. Finally, I make concrete suggestions for constructive uses of technology in teaching and learning.